Analisis Kompetensi Guru Dalam Melaksanakan Manajemen Kelas Pada Pembelajaran Tematik Di SD Negeri Klampok 01 - Dian Evina; Diah Sunarsih; Laelia Nurpratiwiningsih (Jurnal Ilmiah Wahana Pendidikan, 2022)
Teacher pedagogic competence is an ability that must be possessed by every private teacher in managing learning so that it is more systematic and can achieve the planned goals. Objective: This study aims to describe the pedagogical competence of teachers in implementing classroom management in thematic learning. Methods: the research was conducted with data collection techniques using interviews, observation and documentation. Results: the results of the analysis show that the pedagogic competence of teachers in implementing management in thematic learning at SD Negeri Klampok 01, especially in the lower grades has been carried out well, but special attention is needed for third grade teachers in planning the use of media and teaching aids as well as allocating learning time as well. must be considered by grade II and III teachers so that learning remains effective. The factors that support teachers in the implementation of classroom management are influenced by the existence of internal factors from the students' personalities and factors that are external to students' personal support. For the inhibiting factor, namely from the individual students and teachers and group problems that occur in the classroom.